Teachers' Perspectives on Handling Socio-Political Issues in the Classroom - Karna, Wioleta; Stefaniuk, Ireneusz (Iranian Journal of Educational Sociology, 2022)
Purpose: This qualitative study explores the perspectives of teachers on integrating socio-political issues into classroom discussions, aiming to understand the challenges and strategies employed by educators in various educational contexts. The objective was to illuminate the factors influencing effective teaching practices concerning socio-political topics, thereby informing educational policies and teacher training programs.Methodology: This study utilized a qualitative research design, with data collected exclusively through semi-structured interviews involving 30 teachers from different educational levels and geographic locations. Participants were selected using purposive sampling to ensure a diversity of experiences and perspectives. Data analysis was performed using NVivo software to facilitate thematic analysis, ensuring theoretical saturation was achieved to validate the consistency and comprehensiveness of the findings.Findings: The analysis revealed three main themes: Teacher Preparedness, Student Engagement, and Institutional Support. Under Teacher Preparedness, subthemes included Training and Professional Development, Personal Comfort with Topics, and Curriculum Integration, indicating the need for improved resources and training. Student Engagement was characterized by varying levels of participation and the impact of classroom dynamics on learning, highlighting the influence of teaching methods and environment. Institutional Support emerged as critical, with subthemes like Administrative Guidance and Resources emphasizing the need for stronger institutional backing and adequate resources to support teachers.Conclusion: The study underscores the complexities of discussing socio-political issues in educational settings and the pivotal role of teachers in facilitating these discussions. Effective socio-political education requires comprehensive teacher training, supportive institutional frameworks, and resources that together foster an environment conducive to open and critical discussions. Addressing these factors is crucial for preparing students to participate thoughtfully in democratic processes.